2021
DOI: 10.3201/eid2709.204596
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Coronavirus Disease Outbreak among Crewmembers on Cruise Ship, Nagasaki City, Japan, April 2020

Abstract: S evere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was fi rst reported from Wuhan, China (1), and led to outbreaks of coronavirus disease (COVID-19), which was declared a pandemic by the World Health Organization on March 11, 2020. COVID-19 also has been affecting global economies, leading to several recessions (2). Japan experienced an outbreak of COVID-19 on the cruise ship Diamond Princess during the early stages of the epidemic in February 2020 (3-5). The government of Japan prohibited entry int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 23 publications
(18 reference statements)
0
28
0
1
Order By: Relevance
“…The first COVID-19 case in Nagasaki Prefecture was reported on Iki Island on March 14, 2020. The most challenging situation in Period 1 occurred on the foreign cruise that anchored near the quay of Nagasaki harbor in April [ 25 ]. The prospective space-time scan statistic identified four clusters with statistical significance ( p < 0.05), shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first COVID-19 case in Nagasaki Prefecture was reported on Iki Island on March 14, 2020. The most challenging situation in Period 1 occurred on the foreign cruise that anchored near the quay of Nagasaki harbor in April [ 25 ]. The prospective space-time scan statistic identified four clusters with statistical significance ( p < 0.05), shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The present study investigated the evolution of SARS-CoV-2 strains in the second large cruise ship cluster in Japan on the Costa Atlantica (CA). Recently, an epidemiological study revealed the relationships of SARS-CoV-2 infections with age, occupation, underlying diseases, symptoms, and cabin room location on the CA cruise ship [18]. In this previous study, the first case of a body temperature >37.1 โ€ข C was identified on 22 March 2020, in a crew member who belonged to the entertainment group that boarded the CA cruise ship from Europe on March 18 or 19 [18].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, an epidemiological study revealed the relationships of SARS-CoV-2 infections with age, occupation, underlying diseases, symptoms, and cabin room location on the CA cruise ship [18]. In this previous study, the first case of a body temperature >37.1 โ€ข C was identified on 22 March 2020, in a crew member who belonged to the entertainment group that boarded the CA cruise ship from Europe on March 18 or 19 [18]. Our BLAST analysis using the sequences of CA strains located at the root in the phylogenetic tree revealed that the possible origin of CA strains was derived from European countries, showing a high consistency of our results with the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'20๋…„ 1์›” ์ฝ”๋กœ๋‚˜19 ํŒ๋ฐ๋ฏน ์ดํ›„, ์ „์„ธ๊ณ„์ ์œผ๋กœ ๊ต์œก์‹œ์„ค, ์ข…๊ต์‹œ์„ค, ๋ชฉ์š•ํƒ• ๋ฐ ์Œ์‹์  ๋“ฑ ๋‹ค์ค‘์ด์šฉ์‹œ์„ค, ๋ณ‘์› ๋ฐ ์‚ฌ์—…์žฅ ๋“ฑ ๋‹ค์–‘ํ•œ ์žฅ์†Œ์™€ ๊ฒฝ๋กœ๋ฅผ ํ†ตํ•œ ์ง‘๋‹จ ์‚ฌ๋ก€ ๋ฐœ์ƒ์ด ๋ณด๊ณ ๋˜๊ณ  ์žˆ ๋‹ค [3][4]. ์ฝ”๋กœ๋‚˜19์— ์˜ํ•œ ๋‹ค์–‘ํ•œ ์ง‘๋‹จ ์‚ฌ๋ก€ ์ค‘ ์„ ๋ฐ•์—์„œ์˜ ์ฝ”๋กœ๋‚˜19 ์ง‘๋‹จ ๋ฐœ๋ณ‘์€ ์ผ๋ณธ์—์„œ 2020 ๋…„ 2์›” ์ค‘์ˆœ ํƒ‘์Šน์ž 700์—ฌ ๋ช…์ด ๊ฐ์—ผ๋œ D์‚ฌ์˜ ํฌ๋ฃจ์ฆˆ์„  ์‚ฌ๋ก€๊ฐ€ ์žˆ์œผ๋ฉฐ, ์ดํ›„ ๋ฏธ๊ตญ G์‚ฌ์˜ ํฌ๋ฃจ์ฆˆ ์„ , ๋ธŒ๋ผ์งˆ์˜ ํ™”๋ฌผ์„  ๋“ฑ์˜ ์‚ฌ๋ก€๊ฐ€ ๋ณด๊ณ ๋˜์—ˆ์œผ๋ฉฐ [5][6][7], ํŠนํžˆ ํ•ญ๊ณต ๋ชจํ•จ(aircraft carrier)์„ ๋น„๋กฏํ•œ ๊ตฐ ํ•จ์—์„œ์˜ ์ฝ”๋กœ๋‚˜19 ์ง‘๋‹จ ์‚ฌ๋ก€ [8][9] The adjusted rate ratio was calculated using the Mantel-Haenszel method, which is a weighted average of crude rate ratios from the individual stratumspecific two-by-two tables. 3 Due to the high correlation between age and rank, it was excluded from the calculation of adjusted rate ratio.…”
Section: Introductionunclassified